Simulasi Penerapan Strategi Pembelaajaran Berbasis Kepulauan dalam Pembelajaran IPS Geografi di SMP Negeri 1 Ambon - Asep, Asep; Manakane, Susan Evelin; Partini, Dwi (Universitas Pattimura, 2025)
The implementation of island-based learning at SMP Negeri 1 Ambon aims to improve the quality of education in accordance with the local geographical and cultural characteristics. This community service develops a contextual Geography learning strategy by utilizing technology to enhance student engagement and understanding. The methods include planning, development, implementation, and evaluation through collaborative action research involving lecturers, students, teachers, and pupils. The ICARE learning model is applied alongside information and communication technology and the integration of local culture. As a result, island-based learning improves students’ understanding of the material, motivation, and engagement, while strengthening their connection with the surrounding environment. ICT-based media such as interactive digital maps and geospatial applications effectively facilitate local geographic concepts, while game-based learning adds enjoyment and student activity. However, challenges related to technological infrastructure and teacher training need to be addressed to ensure the program’s sustainability. Overall, this community service significantly contributes to strengthening the quality and relevance of Geography learning at SMP Negeri 1 Ambon in accordance with island conditions